Children’s Health as a Legal Threshold in Armed Conflict: From Normative Protection to Structural Failure in Minab - seyednasseri, mohammadMehdi; Abbasi, Mahmoud (Bioethics and Health Law Journal (BHL), 2026)
The protection of children’s health in armed conflict lies at the intersection of international human rights law, international humanitarian law and global health governance. Although the existing legal framework formally recognizes robust protections for children, there remains a persistent and widening gap between normative commitments and their actual implementation in conflict settings. Against this backdrop, the present study examines the attack on Shajareh Tayyebeh School in Minab as a case through which structural deficiencies in the protection of children’s health become analytically visible. This study employs a descriptive-analytical and normative legal methodology. It first reconstructs the conceptual and doctrinal foundations of the right to health within international legal instruments and humanitarian law principles. It then applies a case-study approach to the Minab incident in order to evaluate the extent to which existing legal obligations are reflected or fail to be reflected in operational realities of armed conflict. The analysis further integrates a structural lens to assess systemic gaps beyond isolated violations. The findings indicate that the current international legal architecture suffers from structural limitations that significantly weaken the protection of children’s right to health in armed conflict. These include fragmented enforcement mechanisms, the marginalization of health considerations in military decision-making processes and the absence of operationalized, health-sensitive standards for assessing legality and proportionality. The Minab case illustrates how these deficiencies converge to produce a situation in which formal legal protections fail to translate into effective safeguards on the ground. The study argues that the existing compliance-oriented framework is insufficient to address the complexity of contemporary armed conflicts. It proposes a conceptual shift toward recognizing children’s health as a normative threshold for legality and legitimacy in the conduct of hostilities. Under this approach, the protection of health is not treated as a secondary humanitarian consideration but as a central evaluative criterion in assessing the lawfulness of military action. The Minab case thus functions not merely as an isolated incident, but as an analytical entry point into the structural crisis of children’s protection in international law.